2011
DOI: 10.14221/ajte.2011v36n9.2
|View full text |Cite
|
Sign up to set email alerts
|

Investigative Primary Science: A Problem-based Learning Approach

Abstract: This study reports on the success of using a problem-based learning approach (PBL)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
24

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(65 citation statements)
references
References 20 publications
1
40
0
24
Order By: Relevance
“…Students' attitude was the most potent contributor while teachers' workload was the least contributor to the prediction. Whereas the result of research according to Etherington (2011) with the title of "Investigative Primary Science": A Problem-based learning Approach who stated that the PBL course had a positive impact on the pre-service teachers' motivation to teach science ideas within a real world context.…”
Section: Discussionmentioning
confidence: 99%
“…Students' attitude was the most potent contributor while teachers' workload was the least contributor to the prediction. Whereas the result of research according to Etherington (2011) with the title of "Investigative Primary Science": A Problem-based learning Approach who stated that the PBL course had a positive impact on the pre-service teachers' motivation to teach science ideas within a real world context.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the study showed that students who learned with problem based learning model in the learning process had an increased literacy than those students who learned with direct instruction model. This is reinforced by the opinions of Etherington (2011), who revealed that the problem based learning deserves a more prominent place in science undergraduate primary education for teachers because the process empowers students and educators to direct the study, define and analyze problems and develop solutions. Limitations found in research are very acceptable, because there is no perfect thing.…”
Section: Discussionmentioning
confidence: 99%
“…Problembased learning is a teaching method that involves a student-centered learning through solving real problems [4]. This is a constructivist learning approach that focuses on students' skills in communicating and collaborating.…”
Section: Problem-based Learning (Pbl)mentioning
confidence: 99%